2013
DOI: 10.5152/balkanmedj.2012.067
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Novel Nafimidone Derivatives on Thermal Hypoalgesia in Mice with Diabetic Neuropathy

Abstract: The worldwide diabetes epidemic has shown no signs of abatement. Its prevalence has more than doubled since 1980 (1). Diabetic neuropathy (DN) is the most common diabetic complication, afflicting over 50% of all diabetics. The possible biochemical pathomechanisms include oxidative stress, activation of the polyol pathway, increased advanced glycation end products (AGEs) and their receptors, impaired ionic homeostasis of cells and activation of protein kinases (PKC and PKA), and mitogen-activated protein kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Suter et al showed that rufinamide, a VDSC blocker, attenuated mechanical allodynia in a mouse model of diabetic neuropathy (10). Kamisli et al also reported that nafimidone oxime ester derivatives are effective in reducing thermal hypoalgesia in diabetic mice (11). Arachidonic acid (AA), a polyunsaturated fatty acid-containing 20-carbon, is released from membrane phospholipids by phospholipase A2 and it undergoes metabolism mediated by COX and lipoxygenases (LOX) (12,13).…”
Section: Drug Biochemistrymentioning
confidence: 99%
“…Suter et al showed that rufinamide, a VDSC blocker, attenuated mechanical allodynia in a mouse model of diabetic neuropathy (10). Kamisli et al also reported that nafimidone oxime ester derivatives are effective in reducing thermal hypoalgesia in diabetic mice (11). Arachidonic acid (AA), a polyunsaturated fatty acid-containing 20-carbon, is released from membrane phospholipids by phospholipase A2 and it undergoes metabolism mediated by COX and lipoxygenases (LOX) (12,13).…”
Section: Drug Biochemistrymentioning
confidence: 99%